Performance study of porous asphalt mixture (PAM) for application in tropical environment - Soh, Chun Wee (2015)
The objective of this study is to achieve an appropriate PAM design that can potentially meet the requirements for specific application. Three different mixes, in addition to a control mix determined from past researches, were designed for the study. PG-76 modified bitumen was used in order to provide adequate adhesion for the mix. The binder content used for all mixes was 5.0% of the total mass of the mix. In addition, granite aggregates of sizes less than 0.075 mm were used as filler for the mix instead of hydrated lime. Standard Marshall specimens were fabricated and compacted using the gyratory compactor. Performance tests such as Marshall Stability test, theoretical maximum density test, permeability test, indirect test and Cantabro test were conducted in order to assess the adequacy of the mix for specific application. An unconventional clogging resistance test was also derived from past researches to observe the mixes’ performance when subjected to clogging. The study reveals that changes in the aggregate gradations significantly affects the performance of the mix. In all, the results from the experiments showed that it is feasible to employ the use of PAM for low-strength, high permeability application. The gradations derived were sufficiently permeable, which satisfies the main benefit of using PAM as a road-paving material. Further research and studies are recommended to build on the study that has been conducted to achieve the optimal gradation for different specific applications.